PENYULUHAN DAN PELATIHAN PEMBUATAN EKO ENZIM DI LINGKUNGAN MASYARAKAT PINGGIR KOTA (PERIURBAN) (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Global warming that triggers climate change, which has become a major issue in the world today, is the result of an increase in the concentration of greenhouse gases in the atmosphere. Household waste, 60% of which is organic waste, contributes significantly to CO2 and methane emissions. Therefore, waste management (reduce and reuse) will contribute to the reduction of greenhouse gas emissions. One way to use organic waste is to convert fruit and vegetable waste into eco-enzyme. Eco-enzyme produced from the fermentation of household waste is multi-purpose liquid, which can be used for environmental improvement such as air purifiers and public water purifiers and for household purposes as fertilizers and plant repellents, drain cleaners, external medicine and other various uses. This community service activity aims to socialize eco-enzyme through extension education and training on its manufacture. The extension education which was accompanied by the practice of making eco-enzymes succeeded in increasing the knowledge of participants from close to zero to a value of 71 – 89 in the range of 0 – 100. The use of eco-enzymes resulting from the training was mainly for agriculture (yard plants) and household purposes, while the use for environmental quality enhancement was in the lowest order.